Analisis Determinan Kinerja Bisnis Wirausaha Mahasiswa Di Masa Pandemi Covid-19 - Kusnilawati, Nunik; Santoso, Aprih (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2021)
This study aims to analyze and empirically examine the effect of personal characteristics, human capital, and social capital variables on entrepreneurial business performance variables, with the intervening variable being entrepreneurial characteristics. A sample of 182 respondents, using a questionnaire instrument, the assumption test shows the results of the evaluation of the normality of the data that do not deviate, then the multivariate outliers test has the same degree of freedom of 22, the value of mahalanobis distance ² (0.001;22) = 48.268 so it can be concluded that the model on the data has has no outliers. Residual testing, after the model respecification technique was carried out, it showed that the loading factor of all indicators was > 0.5 and the standardized residual value showed that the value was in the range of ± 2.58 so that it was concluded that the modified model was acceptable. Hypothesis testing, there is a significant influence between the variables of personal characteristics and human capital, on entrepreneurial characteristics. Human capital variables and business characteristics have a significant effect on business performance. But there is no significant effect between the variables (1) social capital on entrepreneurial characteristics, and (2) personal characteristics on business performance. Novelty is a business performance research model with entrepreneurial characteristics as the intervening variable, and the survey was conducted during the economic crisis due to the covid-19 pandemic. Key words : personal characteristics, human capital, social capital, entrepreneurial characteristics, entrepreneurial business performance